2007
DOI: 10.1007/s00467-007-0694-9
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab therapy for juvenile-onset systemic lupus erythematosus

Abstract: Rituximab (RTX), an anti-CD20 monoclonal antibody, has been proposed for use in the therapy of systemic lupus erythematosus (SLE). We present the initial long-term experience of the safety and efficacy of rituximab for treatment of SLE in children. Eighteen patients (mean age 14±3 years) with severe SLE were treated with rituximab after demonstrating resistance or toxicity to conventional regimens. There was a predominance of female (16/18) and ethnic African (13/18) patients. All had lupus nephritis [World He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
1
24

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 25 publications
7
49
1
24
Order By: Relevance
“…Marks et al (2005) and Podolskaya et al (2008) reported that 7 patients with median age of 14.8 years received a dose of 750 mg/m 2 (about up to 100 mg, the maximum dose was 1 g) on Days 1 and 15. The participants in Nwobi et al (2008)'s study took a dose of 188 and 375 mg/m 2 . Similar to the adult patients, most of the pediatric patients were administered methylprednisolone prior to the injection of rituximab; oral prednisolone was decreased gradually after rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marks et al (2005) and Podolskaya et al (2008) reported that 7 patients with median age of 14.8 years received a dose of 750 mg/m 2 (about up to 100 mg, the maximum dose was 1 g) on Days 1 and 15. The participants in Nwobi et al (2008)'s study took a dose of 188 and 375 mg/m 2 . Similar to the adult patients, most of the pediatric patients were administered methylprednisolone prior to the injection of rituximab; oral prednisolone was decreased gradually after rituximab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The two studies reported five cases of herpes zoster. In Nwobi et al (2008)'s study, 14 of the 15 patients achieved complete/partial remission and decreases in SLEDAI, proteinuria, Scr, and prednisone dose. Rituximab was well tolerated in most pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Вопрос применения ритуксимаба в схемах терапии СКВ остается открытым. С одной стороны, в единичных слу-чаях, а также при анализе серии клинических наблю-дений показана эффективность препарата у пациентов с очень высокой активностью СКВ, резистентных к пред-шествующей терапии и высоким риском летального исхода [38][39][40]. С другой стороны, в немногочисленных ретроспективных исследованиях нет указаний на суще-ственное превосходство схем с применением ритукси-маба по отношению к схемам лечения без него [41,42].…”
Section: обмен опытомunclassified
“…У всех пациентов отмечались высокая актив-ность заболевания с развитием жизнеугрожающих состоя-ний, низкая эффективность стандартных методов терапии. Согласно этим исследованиям предложено две схемы вве-дения РТМ, продемонстрировавшие свою эффективность и безопасность: 375 мг на 1 м 2 поверхности тела на протя-жении 4 последовательных недель либо 750 мг на 1 м 2 с ин-тервалом в 2 нед [90][91][92][93][94][95].…”
Section: рекомендация 4 при наличии гемолитической анемии показано дunclassified